Controlling Transformer Magnetizing Offset Current in Isolated Phase-Shift Full-Bridge Converters Using a Luenberger Observer - Angelika Neumann; Sönke Meynen; Ahmad Rahmoun; Daniel Ziegler; Thomas Kirchartz (International Transactions on Electrical Energy Systems)
This paper proposes a flexible digital control scheme for isolated phase-shift full-bridge (PSFB) converters. The required transformer suffers from inevitable imbalance of magnetic flux resulting in an increased magnetizing DC-offset current that threatens system reliability due to saturation effects. The paper addresses two major issues of the occurrence of a magnetizing DC-offset current. First, caused by the change of duty cycle due to output power regulation and second caused by initial manufacturer tolerances of devices. In contrast to common methods the novel control scheme uses a Luenberger observer to estimate the magnetizing current requiring only simple measurement of transformer voltages without additional and lossy auxiliary networks. The observer model, in combination with a PI-controller, directly interventions the duty cycle and removes any DC-offset current resulting from both issues. A detailed deviation of the state-space model of the transformer and a subsequently design of the observer are presented. Simulation and experimental results on a PSFB prototype verify the principal functionality of the proposed control scheme to prevent transformer saturation.